Sokyryntsi Park as the embodiment of the "double life" of the Galagan family - Ivashko, Yulia; Chernyshev, Denys; Sandu, Ioan Gabriel; Dmytrenko, Andrii; Hryniewicz, Małgorzata (Landscape Architecture and Art, 2022)
The history and principles of planning the park of the aristocratic country residence of the Galagan family – "Sokyryntsi" are described. Compared to such parks as Oleksandriia and Sofiivka, Sokyryntsi Park is much less well-known, although it is a unique intermediate link between the "official" parks of Classicism-Empire style, such as Oleksandriia in Bila Tserkva and "private" "Ossian parks", as Sofiivka Park in Uman. Although in some sources Sokyryntsi Park with a complex of buildings and structures belongs to the Empire style, but a deeper analysis has shown the simultaneous presence of components characteristic of the "English Landscape Park" and "Ossian Park". The Sokyryntsi ensemble is a unique example in terms of its division into three zones – "parade", "memorial", closed from strangers, and "recreational" on the shores of reservoirs. In addition, this is a rare example of the location directly on the estate of two churches, family crypts and the house of the estate founder. The Sokyryntsi ensemble is a unique example of how the "double life" of the family was subconsciously embodied in the planning and development of the park, where the "parade" part testified to the education of the owners and their role in the Russian Empire, instead, the hidden "memorial" part acted as a "figure of silence" about the shameful deeds of the estate founder. The methods of historical and culturological analysis, method of comparative analysis, method of field surveys with the implementation of dimensional drawings and photofixation were used.